PERAN TENAGA PELAKSANA ELIMINASI DALAM PELAKSANAAN PROGRAM PEMBERIAN OBAT SECARA MASSAL (POPM) FILARIASIS DI KOTA PEKALONGAN - Herlysse Jorghi BP; Praba Ginandjar; Nissa Kusariana; Lintang Dian Saraswati (Jurnal Kesehatan Masyarakat (Undip), 2019)
Filariasis is a disease caused by filarial worms, Pekalongan City has carried out filariasis MDA (Mass Drug Administration) since 2011-2015. However, the results of the Finger Blood Survey (SDJ) showed that the microfilaria rate was > 1%. This study aims to describe the role of Elimination Personnel (EP) and the obstacles faced in implementing filariasis MDA in Pekalongan City. This study used a cross sectional research method. Sampling in this study used simple random side, total 95 respondents. Data obtained by structure interviews using questionnaires. The results showed that EP in selecting the target family members to be treated is optimal (63.2%). EP in helping puskesmas determine the dosage and administration of medicines for each of the assisted families (52.6%). EP in recording the assisted families who drank the medicine on the card was optimal (55.8%). EP in monitoring and recording treatment reactions that may arise and reporting to health workers was optimal (61.1%).